Staffing the Hospitals : An Urgent National Need - Great Britain. Ministry of Labour and National Service. (London : Published for the Minister of health, the Secrerary of State for Scotland and the Minister of labour and national service by H.M.S.O., 1945)
1945 1945 1940s 20 pages 15 When agreements have been reached by the National Joint Council hospitals will comply in full with their provisions. In the meantime they should continue to observe the provisions of any negotiated agreements to which they are party and should otherwise conform to the following conditions so far as practicable. 2. Wages — At the present time varying standards of wages are operative in the hospital service. The National Joint Council will proceed without delay to endeavour to secure a measure of uniformity on a basis which will ensure adequate remuneration being paid throughout the hospital service. Where no negotiated agreements already exist hospital authorities should, pending agreement by the National Joint Council, take steps to ensure that the wages paid to their domestic staffs are fair and reasonable. 3. Hours of Work — The hours of work of domestic staff in hospitals must be regulated and brought into line with the working conditions in other services in which agreed standard working hours are operative. The National Joint Council will doubtless give early attention to this matter. Where hospitals are unable because of shortage of staff to avoid working hours in excess of a normal working week overtime rates should be paid for the excess hours worked. 4. Off-duty. — All domestic workers should have at least one complete day off each week, and the arrangements should provide for periodic week-end leave of absence. Off-duty hours on other days should be continuous and should be planned well in advance so that the staff can arrange in good time to make full use of these hours. As soon as sufficient staff is available consideration should be given to the institution of straight shifts. 5. Holidays. — The regulation of holidays will be a matter for the consideration of the National Joint Council. Pending the issue of agreed recommendations by the Council all hospital authorities should give their domestic workers an annual holiday with pay plus the equivalent of six statutory holidays. A rota of annual holidays should be prepared well in advance to facilitate the making of holiday arrangements and these arrangements should not be disturbed except in a serious emergency. 6. Health. — Sick leave arrangements will be embodied in the agreements negotiated by the National Joint Council. All Hospitals should have a definite scheme for health supervision for resident domestic staff of which the following may be taken as an outline :— (a) All domestic workers whose work is likely to bring them into contact with infection should have some preliminary instruction about the facts of infection, the paths by which it may be conveyed and the precautions which must be taken to avoid the risks inseparable from their work. They should be afforded the best available means of protection against any illness or infection with which their work may bring them into contact (e.g. diphtheria immunisation). (b) In case of sickness resident domestic workers should be expected to report immediately ; should be seen by a physician at once, and should not return to duty until passed fit for duty by the physician. Regular consulting hours should be fixed and resident domestic workers should be able to approach the physician for a private consultation if they so desire. (c) Suitable and adequate sick bay accommodation should be provided for resident domestic workers suffering from minor ailments. Those requiring treatment which cannot be provided in the sick bay should be transferred to ward beds. (d) Workers to be employed in tuberculosis hospitals and sanatoria on work in tuberculosis wards or in the handling of patients' equipment or bedding before it has been disinfected should have a medical examination with the appropriate tests before being employed and at regular intervals of not more than six months during their employment. 126/TG/RES/X/1036A/4